Control of Acid Phosphatases Expression from Aspergillus niger by Soil Characteristics - Nahas, Ely [UNESP] (Inst Tecnologia Parana, 2015)
This work studied the acid phosphatase (APase) activity from culture medium (extracellular, eAPase) and mycelial extract (intracellular, iAPase) of Aspergillus niger F111. The influence of fungus growth and phosphate concentration of the media on the synthesis and secretion of phosphatase was demonstrated. The effects of pH, substrate concentration and inorganic and organic compounds added to the reaction mixture on APase activity were also studied. Both enzymes were repressed by high concentrations of phosphate. Overexpression of iAPase in relation to eAPase was detected; iAPase activity was 46.1 times higher than eAPase. The maximal activity of eAPase was after 24h of fungus growth and for iAPase was after 96h. Optimal pH and substrate concentrations were 4.5 and 8.0 mM, respectively. Michaelis-Menten constant (Km) for the hydrolysis of p-nitrophenyl phosphate was 0.57 mM with V-max = 14,285.71 U mg(-1) mycelium for the iAPase and 0.31 mM with V-max = 147.06 U mg(-1) mycelium for eAPase. Organic substances had little effect on acid phosphatases when compared with the salts. Both the APases were inhibited by 10 mM KH2PO4 and 5 mM (NH4)(2)MoO4; eAPase was also inhibited by 1 mM CoCl2.
Keywords: Enzyme inhibitors; molybdenum; overexpression; phosphate; soil chemical characteristics